Effects of eccentric versus concentric contractions of the biceps brachii on intracortical inhibition and facilitation. (3rd December 2018) - Latella, Christopher; Goodwill, Alicia M.; Muthalib, Makii; Hendy, Ashlee M.; Major, Brendan; Nosaka, Kazunori; Teo, Wei‐Peng
Abstract : Differences in the neural mechanisms underpinning eccentric (ECC) and concentric (CON) contractions exist; however, the acute effects of fatiguing muscle contractions on intracortical and corticospinal excitability are not well understood. Therefore, we compared maximal ECC and CON contractions of the right biceps brachii (BB) muscle for changes in corticospinal excitability, short‐ (SICI) and long‐interval intracortical inhibition (LICI) and intracortical facilitation (ICF) up to 1 hour post‐exercise. Fourteen right‐handed adults (11 M/3F; 26.8 ± 2.9 year) undertook a single session of 3 sets of 10 maximal ECC or CON contractions (180‐second rest between sets) on an isokinetic dynamometer (40°/s) separated by 1 week, in a randomized crossover study. Maximum voluntary isometric contraction torque (MVIC), maximal muscle compound waves (MMAX ), and motor‐evoked potentials elicited through transcranial magnetic stimulation (TMS) were recorded via surface electromyography from the right BB. MVIC decreased ( P < 0.001) immediately after ECC and CON contractions similarly, but the decrease was sustained at 1 hour post‐ECC contractions only. MMAX was reduced immediately ( P = 0.014) and 1 hour post‐exercise ( P = 0.019) only for ECC contractions. SICI and ICF increased immediately after ECC and CON contractions ( P < 0.001), but LICI increased only after ECC contractions ( P < 0.001), and these increases remained at 1 hour post‐ECC contractions only. These findings suggest that ECC contractions induced a longer‐lasting neuromodulatory effect on intracortical inhibition and facilitation, which could indicate a central compensatory response to peripheral fatigue.